Risk assessment of occupational exposure to BTEX in the National Oil Distribution Company in Iran - Ehsan Partovi; Mona Fathi; Mohammad Javad Assari (Chronic Diseases Journal, 2016)
BACKGROUND: This study evaluated the quantitative, carcinogenic and non-carcinogenic risk of exposure to BTEX using lifetime cancer risk (LCR) and hazard quotient (HQ) in the National Company for Distribution of Petroleum Products in Iran.